Semaglutide in the treatment of obesity and overweight (Research, Society and Development, 2023)
Introduction: The increasing prevalence of obesity in recent decades has become a major health problem worldwide. Semaglutide 2.4 mg once weekly was approved by the FDA in June 2021 for the treatment of overweight/obese individuals. The purpose of this study is to investigate the efficacy and safety of semaglutide in the treatment of obesity in patients who do not have diabetes mellitus. Methodology: This is an integrative literature review that qualitatively addresses the efficacy of semaglutide in the treatment of obesity and overweight. The guiding question was: "Is semaglutide effective in the treatment of obesity and overweight? The search occurred in the main databases, using the descriptors "semaglutide", "obesity", and "overweight". After applying all inclusion and exclusion criteria, a sample of 6 studies was obtained. Results and discussion: The articles exposed in this study served to consolidate the safety and efficacy of the use of subcutaneous semaglutide at a dose of 2.4 mg in non-diabetic patients in order to promote weight loss and reduce cardiometabolic risk. This medication has been shown to be superior to placebo and to another GLP-1 agonist, liraglutide. The main adverse effects are gastrointestinal reactions such as nausea and diarrhea, which tend to decrease over time, as observed in clinical trials. Conclusion: The use of semaglutide has proven safe at the dose of 2.4 mg recommended by the FDA and consolidated by several clinical trials conducted in recent years.